Epigenetics and Breast Cancers - An T. Vo; Richard M. Millis (Hindawi Limited, 2012)
Several of the active compounds in foods, poisons, drugs, and industrial chemicals may, by epigenetic mechanisms, increase or decrease the risk of breast cancers. Enzymes that are involved in DNA methylation and histone modifications have been shown to be altered in several types of breast and other cancers resulting in abnormal patterns of methylation and/or acetylation. Hypermethylation at the CpG islands found in estrogen response element (ERE) promoters occurs in conjunction with ligand-bonded alpha subunit estrogen receptor (Erα) dimers wherein the ligand ERα dimer complex acts as a transcription factor and binds to the ERE promoter. Ligands could be 17-β-estradiol (E2), phytoestrogens, heterocyclic amines, and many other identified food additives and heavy metals. The dimer recruits DNA methyltransferases which catalyze the transfer of methyl groups from S-adenosyl-L-methionine (SAM) to 5'-cytosine on CpG islands. Other enzymes are recruited to the region by ligand-ERα dimers which activate DNA demethylases to act simultaneously to increase gene expression of protooncogenes and growth-promoting genes. Ligand-ERα dimers also recruit histone acetyltransferase to the ERE promoter region. Histone demethylases such as JMJD2B and histone methyltransferases are enzymes which demethylate lysine residues on histones H3 and/or H4. This makes the chromatin accessible for transcription factors and enzymes.